If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(z + 4) + 11 = 6z + 35 Reorder the terms: -4(4 + z) + 11 = 6z + 35 (4 * -4 + z * -4) + 11 = 6z + 35 (-16 + -4z) + 11 = 6z + 35 Reorder the terms: -16 + 11 + -4z = 6z + 35 Combine like terms: -16 + 11 = -5 -5 + -4z = 6z + 35 Reorder the terms: -5 + -4z = 35 + 6z Solving -5 + -4z = 35 + 6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-6z' to each side of the equation. -5 + -4z + -6z = 35 + 6z + -6z Combine like terms: -4z + -6z = -10z -5 + -10z = 35 + 6z + -6z Combine like terms: 6z + -6z = 0 -5 + -10z = 35 + 0 -5 + -10z = 35 Add '5' to each side of the equation. -5 + 5 + -10z = 35 + 5 Combine like terms: -5 + 5 = 0 0 + -10z = 35 + 5 -10z = 35 + 5 Combine like terms: 35 + 5 = 40 -10z = 40 Divide each side by '-10'. z = -4 Simplifying z = -4
| t^2-18t+60.75= | | 5(7x+3)=15 | | -(7-4b)=16b+17 | | V^3-v^2-16v=-32 | | 4x+2+5x-5=180 | | 2x-9+6x=12x+1+x | | x^7-4=-2 | | 3x+22+140= | | 3a+-5a=2a+4 | | 8x+65=11(x+4) | | 21n^2+107n+105=-7-5n | | 7(x+1)2(6+5x)=7 | | t^2-22t+90.75= | | 100+2x=360 | | 2a-5a=2a+4 | | -7m+3m=17-53 | | 7(x+1)-2(6+5x)=7 | | 0.4x-0.2(60+x)=0.2(40) | | 4/7-(-3/8)= | | -3(0+7)+5*0=-21 | | 4/7-(-3/8) | | 7x+7-12+10x=7 | | 8+4(b-4)=-8+7b | | (-2x^4)+7=2x-3 | | 8x+65=11+x+4 | | a/4-a-2/3 | | 195/x=13 | | (2x+3y+1)dx+(2x+3y-5)dy=0 | | -m-8=12.4 | | 5(5x+12)-20x=-3(4x+4)+12 | | 9y+6x=3x-18 | | 3ln(9x)+3=12 |